Retratos hablados: la representación visual del delincuente a través de la caricatura. Colombia: siglo XIX, principios del XX. - Galindo Pérez, Miguel Adolfo (Anuario de Historia de América Latina, 2025)
This article examines the historical dialogues established between artistic practice and the construction of imaginaries and visual representations of the criminal figure—and those suspected of being criminals—from the mid-19th century to the early 20th century. Through a general selection of criminal caricatures, the following pages analyze the role played by artists and caricaturists as active agents in shaping meanings surrounding individuals’ corporeality via a variety of racial, social, and morphological stereotypes. This study explores how caricature, with its interest in the creation of costumbrista tableaux and political and social satire within the nascent independent Republic, fulfilled a hybrid function of surveillance, control, and identification of social dangers. At the intersection of racial discourses, evolutionary debates, criminological theories, medical practices, and police repression, the production of criminal records constructed a criminal archetype that effectively criminalized social, racial, and electoral identities.